Euphorbia nocens, formerly a variety of Euphorbia hirta (Euphorbiaceae) - Steinmann, Victor W. (Instituto de Ecología, A.C., 2003)
Euphorbia hirta is a widespread species distributed throughout tropical and subtropical regions of the world. Four varieties of this taxon have been recognized, although many authors have chosen to treat one of these, Euphorbia hirta var. procumbens, at the rank of species as E. ophthalmica. In this article it is argued that the varieties of Euphorbia hirta should indeed be treated as species. For this reason, Euphorbia hirta var. nocens is elevated to Euphorbia nocens. This species differs from E. hirta in possessing larger, darker-colored seeds and glomerules of cyathia that are restricted to the ends of the primary branches. It is endemic to Mexico and occurs at elevations of 1500 to 2400 m, primarily in pine-oak forest and resulting secondary vegetation. A morphological description of Euphorbia nocens is given, as well as a list of specimens examined. A key to separate this species from E. hirta, E. lineata, and E. ophthalmica is also provided.